2019
DOI: 10.1016/j.msec.2019.109789
|View full text |Cite
|
Sign up to set email alerts
|

Robust biodegradation of naproxen and diclofenac by laccase immobilized using electrospun nanofibers with enhanced stability and reusability

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 37 publications
2
47
0
6
Order By: Relevance
“…However, it should be noted that due to the open structure of the chitinous matrix and limited deformation of the enzyme structure, only a slight worsening of catalytic properties was observed. Similar observations were made in our previous study concerning adsorption immobilization of laccase on poly(l-lactic acid)-co-poly(ε-caprolactone) electrospun nanofibers [63]. By contrast, in a study by Olajuyigbe et al [64], laccase was immobilized by entrapment using calcium and copper alginate beads.…”
Section: Characterization Of Products Following Immobilizationsupporting
confidence: 85%
“…However, it should be noted that due to the open structure of the chitinous matrix and limited deformation of the enzyme structure, only a slight worsening of catalytic properties was observed. Similar observations were made in our previous study concerning adsorption immobilization of laccase on poly(l-lactic acid)-co-poly(ε-caprolactone) electrospun nanofibers [63]. By contrast, in a study by Olajuyigbe et al [64], laccase was immobilized by entrapment using calcium and copper alginate beads.…”
Section: Characterization Of Products Following Immobilizationsupporting
confidence: 85%
“…Degradation of EDCs using immobilized laccase has been the subject of a number of studies [55,56]. Cerrena unicolor laccase (12 U/5 mL) captured on porous silica beads, for example, has been shown to eliminate around 90% of BPA (50 µM) after 60 min of incubation [57].…”
Section: Resultsmentioning
confidence: 99%
“…However, they observed that after 24 h, the EC 30 (the concentration of the drug at which 30% of the microorganisms showed a positive response after the exposure time) values for untreated naproxen and diclofenac solutions amounted around 20% and 25%, respectively. Enzymatic treatment with encapsulated laccase resulted in decreasing the EC 30 values to around 80% and 85% for diclofenac and naproxen, respectively (Zdarta et al 2019). A decrease in the toxicity was also observed by Marco-Urrea et al (2010) and Rodriguez-Rodriguez et al (2011) during the treatment of naproxen effluent using Trametes versicolor.…”
Section: Occurrence Of Naproxen In the Environmentmentioning
confidence: 86%
“…Although low concentrations of naproxen occur in the environment, the increase in its toxicity may be related to a synergy effect with other contaminations. Zdarta et al (2019) examined the toxicity of untreated and enzymatically treated solutions of naproxen and diclofenac against Artemia salina. However, they observed that after 24 h, the EC 30 (the concentration of the drug at which 30% of the microorganisms showed a positive response after the exposure time) values for untreated naproxen and diclofenac solutions amounted around 20% and 25%, respectively.…”
Section: Occurrence Of Naproxen In the Environmentmentioning
confidence: 99%